Economic policies for COVID-19 - Paul Anand (Institute of Labor Economics (IZA), 2020)
This note describes some of the early policy developments in the UK and the way in which the framing and understanding of a novel economic problem evolved to include a focus on livelihoods combining social protection and business support orientations. It highlights various points including the rapid iterative nature of policy development based on consultation in the face of uncertainty, as well as a trade-off between risk-sharing with commercial banks to limit adverse selection and the rapid prevention of insolvencies. We consider some of the policy-making lessons to date and conclude with suggestions for issues that policy makers might consider to support workers in the near and medium term.
Keywords: A1; D7; D8; J00; H; P1; 330; COVID-19; furlough; fiscal response; labour market policy; workers; social contract